The fisheries productivity of purse seine in TPI Kranji Paciran, Lamongan - Elasari, Nova; Sawiji, Asri; Muslih, Toha (UIN Sunan Ampel Surabaya, 2021)
Fisheries productivity plays an important role in national development. The potential of fisheries in Indonesia is quite large so that many coastal communities depend on their lives from fishing activities. East Java province has a fishery area that is quite potential with the availability of considerable human resources, one of them is Lamongan. This research was conducted in Fish Auction Site (Tempat Pelelangan Ikan, TPI) Kranji, Lamongan. The purpose of this study is to find out the productivity value of purse seine fisheries in TPI Kranji based on the size of the ship and the fishing trip. This research was conducted by survey method to know the condition of purse seine fishery in the field directly. Purse seine fishing vessels located in TPI Kranji in 2020 as many as 32 ships that have gross tonnage (GT) of 9 to 24 GT. The dominant catches are Longtail Tuna (Thunnus tonggol), Mackerel Tuna (Euthynnus affinis), Fringescale Sardinella (Sardinella fimbriata), Short Mackerel (Rastrelliger brachysoma) and Goldstripe Sardinella (Sardinella gibbosa). There are two seasons in the fishing process at TPI Kranji, the regular season (Fringescale Sardinella) and the peak season (Tuna). The highest value of productivity per trip was obtained 1.59 tons / trip / year which occurred in 2019 with 223 of fishing trips and the amount of catch production of 356.71 tons. The highest value of productivity per GT occurred in 2020, obtained 2.09 tons / GT / year, which currently has 32 purse seine vessels. The productivity per GT from year to year is increasing because the amount of production is also increasing every year.